PENGUNGKAPAN-DIRI DALAM KOMUNIKASI - Parapat, Nelson Halong (Istek Widuri Jakarta, 2018)
This paper presents a description of the concept of self-disclosure in communication. Everyone likes or dislikes, intentionally or unintentionally, always doing self-disclosure to others. Each of our behaviors that communicate meaning to others is called self-disclosure. Self-disclosure is to reveal information about ourselves. Anything about ourselves that we hide as our secret only, if it is revealed so that known to others then it means we have done self-disclosure.Discussions about self-disclosure include the determinants of self-disclosure, the benefits of self-disclosure, and the risk of self-disclosure. The determinants of self-disclosure are: feelings of liking, large groups, dyadic effects, competence, personality, topics, and sex. The benefits of self-disclosure are: self-knowledge, ability to overcome adversity, communication efficiency, and depth of relationship. Then, the risks of self-disclosure are: personal and social rejection, material loss, intrapersonal difficulties, and loss of well-being.